2015
DOI: 10.2217/cer.15.34
|View full text |Cite
|
Sign up to set email alerts
|

Impact of paliperidone palmitate versus oral atypical antipsychotics on healthcare outcomes in schizophrenia patients

Abstract: PP was associated with comparable overall costs to OAAs, but with significantly lower medical costs, particularly attributable to reduced inpatient visits and long-term care admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 18 publications
6
41
1
Order By: Relevance
“…Consistent with the findings of the current study, the existing literature includes reports of the efficacy of PP with respect to reducing hospitalization rates and costs in patients with schizophrenia compared to placebo [17] and OAT medications [4,10,18]; one of those studies involved a within-patients comparison [9,19]. Our results are consistent with prior findings that once-monthly administration of PP enhances treatment adherence, ultimately reducing the economic burden associated with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the findings of the current study, the existing literature includes reports of the efficacy of PP with respect to reducing hospitalization rates and costs in patients with schizophrenia compared to placebo [17] and OAT medications [4,10,18]; one of those studies involved a within-patients comparison [9,19]. Our results are consistent with prior findings that once-monthly administration of PP enhances treatment adherence, ultimately reducing the economic burden associated with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in agreement with previous retrospective studies which have demonstrated that PP1M is associated with improved adherence [11], reduced hospitalizations [13,14] and lower medical costs [13][14][15] in real-world populations of patients with schizophrenia. Importantly, the present findings highlight consistent trends within the difficult-to-treat subpopulation of patients with schizophrenia and substance-related disorders.…”
Section: Future Science Groupsupporting
confidence: 93%
“…Once-monthly paliperidone palmitate (PP1M) is an LAI that may improve adherence [11], reduce hospitalizations [13,14] and lower medical costs [13][14][15] compared with oral atypical antipsychotics (OAA) among patients with schizophrenia.…”
mentioning
confidence: 99%
“…The results of our study are consistent with the above-mentioned study as well as other previous studies, suggesting that the patients prescribed PP1M had significantly lower discontinuation, switching rates, and non-adherence (calculated by PDC) compared to those prescribed OATs 29,30 . High discontinuation rates among OAT cohort patients may be due to a lack of motivation and cooperation, or the frequent daily administration of the drug compared to PP1M patients who visit a health care professional once a month for the drug administration 10,15,17,31 . Greater adherence to LAI therapy helps physicians make beneficial decisions and distinguishes compliance failure from efficacy failure, which can help to prevent the switching of medications 15,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic drugs form the cornerstone of treatment among patients with schizophrenia in reducing the severity and frequency of acute relapse episodes [6][7][8] 5 ]), are available as oral antipsychotics (OATs) and/or long-acting injectables (LAIs) 9 . Atypical antipsychotics are associated with fewer extra-pyramidal side effects compared to the typical antipsychotics and are therefore the first-line therapeutic agents of choice 6,10 . In practice, non-adherence to OATs is a frequent challenge and common cause of relapse, re-hospitalizations, increased symptom severity, longer inpatient stays, and higher hospital costs in patients with schizophrenia 6 .…”
Section: Introductionmentioning
confidence: 99%